Gerakan Zero Waste Melalui Penyehatan Pantai, Pembangunan Greenhouse Ecobrick, dan Pelestarian Ekosistem Laut dalam Upaya Mewujudkan SDGs 2030 - Jayanti Dian Eka Sari; Syifa'ul Lailiyah; Diansanto Prayoga; Izzato Millati; Ayik Mirayanti Mandagi; Faisal Fikri; Ratih Novita Praja; Diana Agustina; Siti Nur Hilmin; Yunika Tri Yulianti (Universitas Airlangga, 2023)
Background: Banyuwangi Regency is one of the regions in Indonesia which is rich in beach tourism potential, one of which is Pulau Santen Beach which is located in Karangrejo Village, Banyuwangi District, Banyuwangi Regency. However, when the charm of this destination has decreased, the condition of the beach is dirty if left unchecked and no coastal vegetation is carried out, it can damage the marine biota in the vicinity. There is a need for a Santen Island community empowerment program that reviews conservation and sustainable use in order to meet the 14th Sustainable Development Goals (SDGs). Objectives: Community Service entitled